The Impact of the Chinese Rural Healthcare System on Infectious Disease: A Study of the History And Reform of Chinese Healthcare, And the Global Implications of Infectious Disease Control in China - Barbadoro, John (SIT Digital Collections, 2013)
China’s healthcare system has gone through significant changes in the 20th and 21st centuries. These changes have mirrored not only the political focus of the time, but also the social issues facing China. The NRCMCS for rural residents is a cheap annual fee that covers a percentage of medical costs. There are two urban equivalents, the BMIUE and BMIUR for urban employees through their job, and residency respectively. Despite the focus on cheaper healthcare for rural residents, the problems of income inequality and mistrust in the medical system are major problems that affect the health of this large and rapidly growing nation. A result of the inefficiencies in Chinese healthcare has resulted in the emergence of several epidemics in South Eastern China. Avian flu of the mid-20th century, Bird flu in the 1990s, SARS in 2002, and currently H7N9 have all emerged in this region of the world. With the advent of globalization, the spread of infectious disease is now a global problem, one that must promote change in Chinese healthcare, and healthcare systems around the world to help prevent the spread of epidemics.